Verbal and Visual Signs of the Greenpeace Advertisements - Hartadi Jaya Nugraha, I Made; Sukarini, Ni Wayan; Weddha Savitri, Putu (Humanis, 2019)
This study entitled “Verbal and Visual Sign of the Greenpeace Advertisement” is intended to identify the verbal and visual sign presented in Greenpeace advertisement, to find out the messages conveyed in Greenpeace advertisement, and to analyze the relations between verbal and visual signs in Greenpeace advertisement. The data in this study were taken from three Greenpeace advertisements inadso ftheworld.com. This study was using documenting method to collect the data and qualitative method to analyze the data. The data were analyzed based on the theory proposed by Barthes as cited in MacEachren (1995), in the two systems of signification which formulates that a sign is a system consisting of expression (E) which relates (relation –R-) to the content (C), the theory proposed by Leech (1972) which focuses on the standard component of press advertisement, and the theory proposed by Halliday and Hassan (1985) in the three features of context of situation. The result of analysis shows that the verbal signs appear as the texts, words, or sentences in the advertisement. On the other hand, visual signs appear as a picture on the advertisement for the message conveyed can be seen from the denotative and connotative meaning of the advertisements. Therefore, verbal and visual advertisements support one another in presenting the message of the advertisement itself.